Leave the world behind : a novel - Alam, Rumaan (Ecco, 2020)
Amanda and Clay head to a remote corner of Long Island expecting a vacation: a quiet reprieve from life in New York City, quality time with their teenage son and daughter, and a taste of the good life in the luxurious home they've rented for the week. The houseowners, Ruth and G. H., arrive in the middle of the night in a panic. They say a sudden blackout has swept the city: the TV and internet are down, and no cell phone service. Is the vacation home, isolated from civilization, a safe place for their families? And are they safe from one other? -- adapted from jacket